Open abdomen: is a dedicated emergency surgery team needed? A single center retrospective study on 141 consecutive patients. Issue 9 (30th July 2022) - Marrano, Enrico; Bunino, Francesca; Del Zotto, Giulio; Ceolin, Martina; Mei, Simona; Brocchi, Andrea; Kurihara, Hayato
Abstract: Background: Open Abdomen (OA) is widely used when facing a catastrophic abdomen. Still, no indication is validated by a strong and high quality of evidence. The study reports the 5 year experience of a dedicated emergency general surgery (EGS) team. Methods: Retrospective observational cohort study. Patients undergoing OA management from 2/01/2015 to 19/07/2020 for trauma, non‐traumatic emergencies or rescue surgery. Results: One hundred and forty‐one patients. Age 66.9 ± 15.1. Male 58.2%.9.3% OA for trauma, 64.5% for non‐traumatic emergencies and 26.2% for rescue surgery. 40.4% performed by the EGS team 52.4% indication for surgery was a severe intra‐abdominal infection. TAC device: commercial negative pressure wound therapy (NPWT) (83%), Sandwich VAC (12%), commercial NPWT with polypropylene mesh (5%) for pregressive fascial traction. Enteroatmospheric fistula (EAF) in 3 patients. OA duration 5.3 days (1–25). A 1.8 revision surgeries (0–12) required for definitive closure; ICU stay 9.9 days (0–78). 30‐day mortality 23.5%. Overall and 1‐year mortality were 47.5% and 43.3%. Overall survival 9.9 months. An increased one‐year mortality rate was found in the >65 group ( P = 0.01). Conclusions: We reported a wide use of OA in septic abdomen (90% of cases). We had a low rate of EAF, short ICU stay and OA duration. These results are related to the fact that patients were treated by a dedicated EGS team, suggesting that OA management should be cared for as much as possible by trained and experienced surgeons. Prospective studies with more accurate patient selection are needed to prove our conclusions. Abstract : Open abdomen is a complex management done in catastrophic abdominal situations. Having a dedicated emergency surgery team managing these patients creates improving results on the type of definitive fascial closure, length of the open abdomen treatment and possible complications.